Microsoft Office Excel 2007 - O'Leary, Timothy J., 1947-; O'Leary, Linda I. (Boston McGraw-Hill/Irwin, 2008)
Stepping into Access; Creating databases and tables; Modifying tables and fields; Working in the table; Retrieving information; Creating forms and using controls...
Includes index.
Keywords: Business -- Computer programs; Electronic spreadsheets; Computers; Tin học; Microsoft Excel (Computer file)